2022
DOI: 10.1021/acs.jmedchem.2c00958
|View full text |Cite|
|
Sign up to set email alerts
|

Rational Design, Synthesis, and Biological Evaluation of Novel S1PR2 Antagonists for Reversing 5-FU-Resistance in Colorectal Cancer

Abstract: Resistance to 5-FU reduces its clinical efficacy for the treatment of colorectal cancer. Sphingosine-1-phosphate receptor 2 (S1PR2) has emerged as a potential target to reverse 5-FU-resistance by inhibiting the expression of dihydropyrimidine dehydrogenase (DPD). In this study, 38 novel S1PR2 antagonists based on aryl urea structure were designed and synthesized, and the structure−activity relationship was investigated based on the S1PR2 binding assay. Representative compound 43 potently interacts with S1PR2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…92 Cancer cells can also overexpress DPD after FBAL stimulation, leading to the degradation of 5-FU that enters the cells, which promotes the development of 5-FU-resistance. 93 Our previous research aimed to investigate the mechanism of intracellular DPD upregulation. We discovered that FBAL, the final metabolite of 5-FU, stimulates S1PR2 on the cancer cell surface, which in turn results in S1PR2 internalization.…”
Section: Inflammatory Bone Loss Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…92 Cancer cells can also overexpress DPD after FBAL stimulation, leading to the degradation of 5-FU that enters the cells, which promotes the development of 5-FU-resistance. 93 Our previous research aimed to investigate the mechanism of intracellular DPD upregulation. We discovered that FBAL, the final metabolite of 5-FU, stimulates S1PR2 on the cancer cell surface, which in turn results in S1PR2 internalization.…”
Section: Inflammatory Bone Loss Diseasementioning
confidence: 99%
“…We discovered that FBAL, the final metabolite of 5-FU, stimulates S1PR2 on the cancer cell surface, which in turn results in S1PR2 internalization. 93 This process leads to the upregulation of DPD expression and rapid degradation of intracellular 5-FU. Our research also identified the involvement of Jumonji domain-containing protein-3 (JMJD3) and histone H3 lysine 27 trimethylation (H3K27me3) in this process.…”
Section: Inflammatory Bone Loss Diseasementioning
confidence: 99%
See 2 more Smart Citations